Trends and strategies of verbal communication in sports training a systematic review of psychological and linguistic perspectives - Daroe Iswatiningsih; Muhammad Andi Setiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Verbal communication significantly influences coaching effectiveness, yet studies bridging psychology and linguistics are limited and lack clarity in mechanisms and features.